2023
DOI: 10.3390/su15086999
|View full text |Cite
|
Sign up to set email alerts
|

Field Investigation and Finite Element Analysis of Landslide-Triggering Factors of a Cut Slope Composed of Granite Residual Soil: A Case Study of Chongtou Town, Lishui City, China

Abstract: Landslides caused by excavations and precipitation events are widespread types of slope failures in southwest Zhejiang, China, in areas with granite residual soil. Investigations of the effect of high precipitation on the hydrological response, stability, and evolutionary mechanism of cut slopes in granite soil areas are lacking. The characteristics of historical landslides in Chongtou Town in southwestern Zhejiang were summarized, and a typical slope was selected for analysis. The hydraulic and mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…AYBE RK KAYA combined kinematics, limit equilibrium, and numerical stability analyses to study the failure mechanism of houses on nearby slopes after the excavation of basalt and tuff tunnels; they confirmed that the slope instability is related to the strength reduction in rock mass and joints after rock mass disturbance [23]. TieSheng Yuan et al utilized Geo Studio to establish a deformation model to validate the conformity of a numerical method and investigate a cut slope [24].…”
Section: Introductionmentioning
confidence: 94%
“…AYBE RK KAYA combined kinematics, limit equilibrium, and numerical stability analyses to study the failure mechanism of houses on nearby slopes after the excavation of basalt and tuff tunnels; they confirmed that the slope instability is related to the strength reduction in rock mass and joints after rock mass disturbance [23]. TieSheng Yuan et al utilized Geo Studio to establish a deformation model to validate the conformity of a numerical method and investigate a cut slope [24].…”
Section: Introductionmentioning
confidence: 94%
“…It has been recognized that uncertainty has a significant influence on the stability of geological structures such as slopes. However, in the stability analysis of unsaturated soil slope, the stratum was usually considered to be deterministic in the past [28][29][30][31][32][33][34][35]. Recently, increasing attention has been paid to the unsaturated slope stability analysis considering the spatial variability of soil properties [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties and stability of GRS are significantly affected by water. Soil disintegration, which refers to the phenomenon of soil fragmentation, breaking, and separation or weakening of its strength in hydrostatic water, is closely related to the resistance of soil to water intrusion and is a critical evaluative indicator of soil erosion [1,[6][7][8][9][10][11]. The prominent disintegration behavior of GRS is responsible for the apparent collapsing erosion of the granite weathering zone, resulting in severe soil erosion and environmental damage, as well as natural geohazards such as landslide and mudslide disasters [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have used the quantitative testing method to evaluate GRS disintegration characteristics and its influential factors, including internal factors (e.g., dry density, initial moisture content, degrees of weathering, structure, and mineral composition) and external factors (e.g., temperature, pH, and dry-wet cycles) [1,[6][7][8][9][10][11][12]15,16,21]. Scholars agree that the initial moisture content significantly affects the disintegration characteristics of GRS.…”
Section: Introductionmentioning
confidence: 99%